Representasi Makna Denotasi Kekerasan Seksual Dalam Film Pendek Profil Pelajar Pancasila Episode Hujan Tak Akan Turun Selamanya - Fikri Ramadhan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Sexual harassment is a form of sexual violence. Several cases of sexual violence in Indonesia occur online. From this case, the Indonesian Ministry of Education and Culture made a short film that raised the theme of online sexual harassment entitled "Profile of Pancasila Students Episode Hujan Tak Akan Turun Selamanya." The purpose of this study was to understand how a film displays acts of online sexual harassment and to analyze the denotative meaning of sexual violence against women in the short film. The type of research used in studying this study was through a qualitative approach. This study uses Roland Barthes' semiotic analysis. The results of this study indicate that there are five denotative meanings of online sexual harassment shown in the short film. The conclusion of this study is that the short film highlights the importance of being careful in sharing personal information in the digital world. This film also emphasizes values ​​such as honesty, courage, and support from those closest to you in dealing with serious problems